Term Offspring of Nulliparous Women Have Lower Weight-for-age Z-scores Than Multiparous Women in Chimaltenango, Guatemala (P11-065-19). (13th June 2019) - Garces, Ana; Perez, Wilton; Figueroa, Lester; Westcott, Jamie; McClure, Elizabeth; Nolen, Tracy; Moore, Janet; Hambidge, Michael; Krebs, Nancy
Abstract: Objectives: Women´s parity may be associated with their current offspring growth outcomes. We aimed to determine the association between parity and birthweight among Guatemalan women. Methods: We analyzed 50, 987 term births that occurred between 2014 and 2016 in the Chimaltenango, Guatemala site of the Global Network for Women and Children's Health Maternal Neonatal Health Registry. Gestational age was determined by ultrasound or last menstrual period. Birthweight was obtained within the first 48 hours of life with up to 10 grams of accuracy and converted to z-scores using INTERGROWTH-21st with quality control. The means of birthweight z-scores were computed by ANOVA; adjusting for maternal age and height did not change the results. P-values < 0.05 were considered significant. Results: Nulliparous women had offspring of lower birthweight than women with parity 1–3 and 4 or more. Conclusions: These results may have implications for the targeting of nutritional interventions aimed to improve pregnancy outcomes. Funding Sources: Grant from National Institute of Child Health and Human Development. Supporting Tables, Images and/or Graphs: